Impurities especially titanium in the rare earth metal gadolinium— before and after solid state electrotransport - 苗睿瑛 张小伟 朱琼 张志琦 王志强 颜世宏 陈德宏 周林 李宗安 (Journal of rare earths, 2014)
Gadolinium was prepared by conventional procedures of fluorination, reduction, distillation and solid state electrotransport（SSE）. The electronegativities of the metals were found to have an important influence on the electrotransport process and result of the impurity element. Meanwhile, titanium particles in the distilled gadolinium as major metallic impurities were studied by high resolution transmission electron microscopy（HRTEM） before and after solid state electrotransport. The results showed that impurities especially titanium transported from anode to cathode during SSE. In the metal before SSE, there were impurities of titanium in strip shape or embedded round shape. After SSE processing, titanium particles in the metal smaller than 50 nm in the cathode, but existed 6 to 10 times bigger in the anode.